Online instructional anatomy videos: Student usage, self‐efficacy, and performance in upper limb regional anatomy assessment. Issue 5 (4th December 2017) - Langfield, Tracey; Colthorpe, Kay; Ainscough, Louise
Abstract : Allied health professionals concur that a sound knowledge of practical gross anatomy is vital for the clinician, however, human anatomy courses in allied health programs have been identified as high‐risk for attrition and failure. While anatomists and clinicians agree that learning anatomy via human cadaveric instruction is the preferred method, students vary in their reaction to the cadaveric learning experience and have differing levels of anatomy self‐efficacy. This study investigated whether student self‐efficacy had an effect on student usage of supplemental instructional videos and whether the use of videos had an impact on student self‐efficacy and/or learning. Anatomy self‐efficacy differed based on gender and prior performance. Student usage of the videos varied widely and students with lower self‐efficacy were more inclined to use the resources. The provision of the videos did not improve overall cohort performance as compared to a historical cohort, however, those students that accessed all video sets experienced a greater normalized learning gain compared to students that used none or one of the four sets of videos. Student reports and usage patterns indicate that the videos were primarily used for practical class preparation and revision. Potentially, the videos represent a passive mode of teaching whereas active learning has been demonstrated to result in greater learning gains. Adapting the videos into interactive tutorials which will provide opportunity for feedback and the development of students' self‐evaluation may be more appropriate. Anat Sci Educ 11: 461–470. © 2017 American Association of Anatomists.